Local Produce, Foreign Labor: Labor Mobility Programs and Global Trade Competitiveness in Canada* - Preibisch, Kerry L. (Rural Sociology, 2007)
Abstract Temporary visa workers are increasingly taking on a heightened profile in Canada, entering the workforce each year in greater numbers than immigrant workers with labor mobility rights (Sharma 2006). This paper examines the incorporation of foreign workers in Canadian horticulture under the Seasonal Agricultural Workers Program (SAWP). I argue that foreign labor supplied under the SAWP secures a flexible workforce for employers and thus improves Canada's trade competitiveness in the global agrifood market. Using multiple research strategies, I track the evolution of Canadian horticulture in the global market and the transformation of labor in this industry. I outline the steady growth in the employment of temporary visa workers in the horticultural industry and show how they have become the preferred and, in some cases, core workforce for horticulture operations. The benefits of SAWP workers to employers include the provision of a workforce with limited rights relative to domestic workers and considerable administrative support in selecting, dispatching, and disciplining workers provided at no cost by labor supply countries. I conclude that the SAWP is a noteworthy example of the role of immigration policy in regulating the labor markets of high-income economies and thus ensuring the position of labor-receiving states within the global political economy.